EFEKTIVITAS EDUKASI KESEHATAN GIGI DENGAN METODE TRAIN THE TRAINERS DALAM MENINGKATKAN PENGETAHUAN GURU DAN WALI MURID SD YAPITA SURABAYA: EFFECTIVENESS OF DENTAL HEALTH EDUCATION USING THE TRAIN THE TRAINERS METHOD IN IMPROVING THE KNOWLEDGE OF TEACHERS AND PARENTS OF YAPITA ELEMENTARY SCHOOL SURABAYA - Andriani, Dwi; Twi Agnita Cevanti; Nora Lelyana; Aprilia; Dianty Saptaswari; Bambang Sucahyo; Dwi Setianingtyas; Nafiah; Henu Sumekar; Arya Brahmanta; Shintya Rizki Ayu Agitha; Sularsih; Yufita Fitriani; Vivin Ariestania; Arifzan Razak (Universitas Hang Tuah Surabaya, 2025)
Dental and oral problems in Indonesian children are caused by low knowledge, comprehension, and behavior that ignores dental and oral health maintenance, resulting in tooth and mouth damage. This activity is in partnership with SD Yapita which is a school supported by the Faculty of Dentistry, Hang Tuah University. The aim is to prepare parents and teachers of Yapita Elementary School students to become ambassadors for oral and dental hygiene so that they can become mentors for their children or students. This method is carried out online and offline from classes 1 to 6 using a simple random sampling technique. The results were statistically analyzed using the Paired T-test. The average pre-test score from the teacher was 60 and the parents were 56, while the post-test result from the teacher was 84 and the parents was 85. The results of the data analysis were normally distributed (p>0.05) followed by the Paired correlation test T-test. The results show a relationship between the pre and post-test of teachers and parents. This shows that this educational activity can increase the knowledge of teachers and parents so that they can become ambassadors of oral and dental hygiene to their children or students.